Free water surface and horizontal subsurface flow constructed wetlands: a comparison of performance in treating domestic graywater - Hollowed, Margaret Ellen, author; Sharvelle, Sybil E., advisor; Roesner, Larry A., committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2012)
Communities throughout the United States and abroad are seeking innovative approaches to sustaining their freshwater resources. Graywater reuse for non-potable demands is gaining popularity because it allows for the reuse of minimally contaminated wash water, generated and treated on site. Graywater is defined as any wastewater generated at the home or office including wastewater from the laundry, shower, and bathroom sinks but excluding water from the toilets, kitchen sinks, and dishwasher. When compared to other wastewater generated in the home, graywater is contaminated with lower concentrations of organics, solids, nutrients, and pathogens. These characteristics make the water suitable for reuse with negligible treatment when compared to other domestic wastewater sources. Graywater reuse for non-potable demands reduces the demand for treated water and preserves source waters. One method of treating graywater at a community scale for irrigation reuse is constructed wetlands. Despite widespread interest in this innovative approach, limited guidance is available on the design and operation of constructed wetlands specific to graywater treatment. The foremost objective of this research was to compare the performance of a free water surface constructed wetland (FWS) to a horizontal subsurface constructed wetland (SF) for graywater treatment and to assess their ability to meet water quality standards for surface discharge and reuse. This was done by comparison of percent (%) mass removal rates and requisite surface areas (SA) based on determined removal rates ( k ). Aerial loading rates were compared to EPA suggested aerial loading rates in an attempt to provide recommendations for target effluent concentrations. Determining contaminant removal rates is important for creating wetland design standards for graywater treatment and reuse. Contaminant removal rates were evaluated over the summer and fall of 2010 and 2011 for a SF wetland. These removal rates were compared to the removal rates evaluated over a two year period (2008-2010) for a FWS wetland. Another objective was to determine the % mass removal of three common anionic surfactants in constructed wetlands (both FWS and SF) and finally, the possibility of incorporating constructed wetlands into greenhouse community garden centers as an option to reduce the losses resulting from evapotranspiration (ET) in arid climates was explored briefly. The results indicate that SF wetlands provide relatively stable and more efficient treatment year round when compared to FWS wetlands. In particular, the SF wetland showed statistically significant higher mass removal of both biological oxygen demand (BOD5 ) and total nitrogen (TN) than the FWS wetland during winter months (P=0.1 and 0.005; α=0.1). When all the seasons were compared for each wetland individually there was a statistically significant degree of removal for BOD5 and TN between the seasons in the FWS wetland (P=0.09 and 0.04; α=0.1) while there was none in the SF wetland (P=1.0 and 0.9; α=0.1). These results are consistent with other findings in the literature. When mass removals were compared to HLRs, the trends support the ability of SF wetlands to function across a wide range of HLRs and climatic conditions, whereas FWS wetlands are less capable of performing well under less than ideal conditions. Results of the k-C* and SA analyses, though limited in their completeness, suggest once again that SF wetlands are capable of increased rates of removal not only during the warm summer months but also during the winter and transition months. Specifically, nitrification and denitrification processes may be contributing to TN removal in the SF wetland, particularly during senescent periods. Surfactant removal was also consistent with findings in the literature, with 50% removal of LAS and greater than 70% removal of AES/AS, suggesting that LAS is more persistent.
Keywords: constructed wetlands; water reuse; graywater